DIGITAL SPIRITUAL ENGAGEMENT: AN INTEGRATIVE REVIEW OF RESILIENCE AND LIFE SATISFACTION - Archana Shori; Prof. Monika Rikhi, DU (IJRDO - Journal of Social Science and Humanities Research, 2026)
The rapid expansion of digital technologies has transformed religious and spiritual practices, giving rise to digital spiritual engagement as a prominent feature of contemporary life. While traditional spirituality has been consistently associated with psychological resilience and life satisfaction, the implications of digitally mediated spiritual practices remain insufficiently synthesised. This integrative review examines the conceptual foundations, theoretical mechanisms, and empirical evidence linking digital spiritual engagement with psychological resilience and life satisfaction. A comprehensive review of interdisciplinary literature published in recent years was conducted, drawing from psychology, sociology, religious studies, and health research. The analysis focused on theoretical models, empirical findings, and emerging themes related to online worship, spiritual coping, community belonging, and subjective well-being. Findings indicate that digital spiritual engagement contributes to resilience through meaning-making, emotional regulation, and perceived social support. These resilience processes, in turn, enhance life satisfaction by fostering purpose, gratitude, and relational connectedness. However, potential risks such as digital fatigue and reduced embodied interaction warrant consideration. Digital spiritual engagement functions as a hybrid psychosocial resource that can promote resilience and life satisfaction in technologically mediated contexts. Future research should employ longitudinal and culturally sensitive approaches to refine the understanding of its long-term effects